Effect of Sediment Filter Pore-Size Variation in a Reverse Osmosis System on Treated Water Quality - Naufal Zuhair Tarim Ramadhan; Deni Fajar Fitriani; Samsudin Anis (Journal of Creativity Student, 2026)
Drinking-water quality is commonly evaluated from its dissolved-solids content, pH, turbidity, and color. Although reverse osmosis (RO) can substantially improve these characteristics, stable performance depends on feed-water conditions and appropriate pretreatment. This experiment examined whether sediment-cartridge pore size altered the quality of water produced by a small RO unit. Cartridges rated at 5, 3, and 1 micrometers were tested. TDS, pH, and turbidity were the primary response variables, while color was included as a supporting indicator. The untreated feed contained 18 mg/L TDS, had a pH of 7.44, turbidity of 0.38 NTU, and color of 11 TCU. Bottled drinking water, assessed only as a benchmark, contained 235 mg/L TDS, had a pH of 7.93, turbidity of 0.07 NTU, and color of 2 TCU. With the 5-micrometer cartridge, the RO product recorded 26 mg/L TDS, pH 7.40, turbidity of 0.05 NTU, and color of 4 TCU. Corresponding results for the 3-micrometer cartridge were 11.3 mg/L, 7.66, 0.53 NTU, and 3 TCU; for the 1-micrometer cartridge, they were 11.7 mg/L, 7.63, 0.57 NTU, and 3 TCU. The 3-micrometer configuration produced the lowest TDS, whereas the 5-micrometer configuration produced the lowest turbidity. Thus, pore-size variation was associated with observable differences under the test conditions. Because measurements were not replicated, these patterns should be verified through repeated trials before a causal effect is inferred.